(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
This article brings a brief reflection about automatic enrolment in occupational and optional pension schemes, considering its advantages and disadvantages. It also reflects about the implementation of automatic enrolment in Brazil. It concludes that automatic enrollment is viable in Brazil, but there is a need to enact an amendment in the current Law.